2019
DOI: 10.3389/fvets.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Yield of Dental Radiography and Cone-Beam Computed Tomography for the Identification of Dentoalveolar Lesions in Cats

Abstract: The objective of this study was to evaluate the diagnostic yield of dental radiography (DR) and 3 cone-beam computed tomography (CBCT) software modules for the identification of 32 pre-defined dentoalveolar lesions in cats. For 5 feline cadaver heads and 22 client-owned cats admitted for evaluation and treatment of dental disease, 32 predefined dentoalveolar lesions were evaluated separately and scored by use of dental radiography and 3 CBCT software modules [multiplanar reconstructions (MPR), tridimensional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
5
9
0
Order By: Relevance
“…Nevertheless, both techniques presented a similar specificity. Our results are consistent with previous studies that reported CBCT as the most accurate method for finding artificial external root resorption compared to panoramic or periapical radiography [13,15,16]. Even though we observed that PR had been found to be less sensitive, a high specificity of PR was obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, both techniques presented a similar specificity. Our results are consistent with previous studies that reported CBCT as the most accurate method for finding artificial external root resorption compared to panoramic or periapical radiography [13,15,16]. Even though we observed that PR had been found to be less sensitive, a high specificity of PR was obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, both techniques presented a similar speci city. Our results are consistent with previous studies that reported CBCT as the most accurate method in nding arti cial external root resorption when compared to panoramic or periapical radiography (13,15,16). Even though, we observed that PR has been found to be less sensitive, a high speci city of PR was obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Cross-sectional imaging techniques such as CT and, more recently, cone beam CT (CBCT) have been considered the gold standard diagnostic imaging techniques for evaluating the TMJ bony structures. 6,[13][14][15][16] MRI has been used for assessment of the TMJ soft tissue structures in the veterinary field but much less frequently than for humans, where it is widely used for assessment of the extra-and intra-articular soft tissue structures, in particular, for evaluation of the morphology and positioning of the articular disc. 17,18 Although surgical excision of the abnormal tissue by gap arthroplasty, condylectomy or wide extra-articular osteotomy are currently the treatment of choice for TMJA, these procedures may be time-consuming, technically challenging and carry a potential risk of iatrogenic trauma and death owing to the complex anatomy surrounding the TMJ.…”
Section: Introductionmentioning
confidence: 99%